STRATEGI KYAI DALAM PEMBENTUKAN AKHLAK TAWADHU’ SANTRI DI PONDOK PESANTREN DARUSYAFAAT - Ahmad Rojali; Sri Utami (Raudhah - Proud To Be Professional, 2024)
ABSTRAK The role of ustadz / Kyai towards students is often in the form of a father's interest. Apart from being a teacher, the kyai also acts as a spiritual leader and is responsible for the development of the personality and physical health of his students. In a more advanced condition, a Kyai stands in the boarding school as the primary figure. Kyai as the main leader, owner and teacher, work is very influential in the pesantren but also affects the community environment and is even heard throughout the archipelago. With a Research Focus; Kyai`s Strategy in the formation of Akhlak Tawadhu’ Santri at the Darusyafa’at Islamic Boarding School Tugu Jaya. The strategy used by the kyai in forming the tawadhu’ character of the students at boarding school is to use an axemplary strategy, namely that a kyai must be able to be a good example for his students and invite them to do good by convincing their students through religious teachings. Then the habituation strategy, namely the kyai can create awareness of his students so that they can make habituation in carrying out mandatory and sunnah worship that has been taught, the study of the yellow book, bandongan, is carried out together and taught directly by the kyai, sorogan iscarried out by personnel for face-to face according to their level.for students who are still beginners, there is a “ta’limul muta’alim” lesson then for the diniyyah madrasah, the “Adabun nisa” book lesson then who has entered 2-3 years, the students are required to follow the Koran interpretation of the jallalain which includes the interpretation of the Koran also explains about adap or manners. Then the students above him recite the “ihya Ulumuddin” Book. Then the last strategy is the civilizing strategy, namely the kyai to increase knowledge and understanding of religion, increase awareness in worship and ancrease changes in attitudes and behavior by conducting breaving or deliberation with his students for maximum results.